Liquid helium free mechanical property test system with G-M cryocoolers. (July 2017) - Zhang, Hengcheng; Xu, Dong; Huang, Rongjin; Huang, Chuanjun; Liu, Huiming; Han, Yemao; Li, Laifeng
Highlights: A liquid helium free mechanical property testing system cooled by G-M refrigerators was developed and studied. The method of decompression cooling is adopted, which helps to decrease the sample temperature. The sample can be cooled from room temperature to minimum temperature 2.7 K in about 7.5 h. This system can be installed onto an electronic universal testing machine or a fatigue testing machine to characterize static tension, fracture mechanics or fatigue properties at tunable low temperatures. Abstract: In the present work, a cryogenic mechanical property testing system conduction-cooled by two G-M cryocoolers was developed. The testing sample can be cooled from room temperature to 2.7 K within 7.5 h. The sample was first cooled down to 11.1 K directly by the two G-M cryocoolers and then cooled down to 2.7 K by decompressing the chamber. Instead of liquid helium, the cooling process is characterized by cooling with recycled helium gas as heat transfer medium. The heat load of the system was analyzed and optimizations were adopted in terms of material selections and design. The static load capacity of the system reaches 200 kN and the fatigue load capacity can reach 50 kN. This system can be installed onto an electronic universal testing machine or a fatigue testing machine to characterize static tension, fracture mechanics or fatigue properties at tunable low temperatures. Tensile properties of 316L austenitic stainless steels at 4.2 K were tested with the system and the results were compared with those obtained by cooled using liquid helium, which demonstrates high reliability.